OCEANIC ORE-BEARING FERROBASALTS: PHYSICOCHEMICAL CONDITIONS OF FORMATION - Sharapov V.N.; Zhmodik A.S. (My University, 2000)
Statistical study of basalts from mid-ocean ridges differing in spreading rate shows that two main petrochemical groups of basalts, N-MORB and ferrobasalts, are zonally distributed along ang across their crest. Ferrobasalts are all basalts "enriched" in Fe and Ti as compared with N-MORB. Of them, 1 to 5% may have high concentrations of sulfide and sulfide-oxide drop-like ore segregations. Hydrothermal ore-forming systems are spatially conjugate with regions of development of ferrobasalts enriched in water and magmatic minerals. Ferrobasalts with high concentrations of liquation drop-like segregations that occur in volcanogenic sections of the Earth's crust of the MOR crest are the products of fractionation of basic melts in shallow intrusive chambers. Water- and chlorine-enriched ferrobasalt melts may be the products of crystallization differentiation of E-MORB-type basic liquids. Estimation of the physicochemical and polybaric conditions of fractionation of petrogenetic components shows that, given magma crystallinity is no more than 0.3, melts of ferrobasalt composition may form under pressures less than 5 kbar in a wide range of varying partial pressures of oxygen during fractionation of both picritoid and tholeiitic magmas.